Transcriptomic and Metabolomic Profiling Reveals the Protective Effect of Acanthopanax senticosus (Rupr. & Maxim.) Harms Combined With Gastrodia elata Blume on Cerebral Ischemia-Reperfusion Injury - Lin, Bingfeng; Chen, Renhao; Wang, Qi; Li, Zhifeng; Yang, ShiLin; Feng, YuLin (Frontiers in Pharmacology, 2021)
The effects of current treatment strategies used in ischemic strokes are weakened by cerebral ischemia-reperfusion (CIR) injury. Suitable treatment regimens targeting CIR injury are still lacking. Two herbs that have been used as Traditional Chinese medicine, namely, Acanthopanax senticosus (ASE) and Gastrodia elata Blume (GEB), are indicated in treating stroke and other cerebrovascular diseases. However, there are no studies that report the effects ASE combined with GEB in the treatment of CIR injury. In our study, we used the Zea Longa method to induce CIR injury in male Wistar rats. We conducted pharmacodynamic studies and found that co-administration of ASE and GEB may improve neuronal injury and prevent neuronal apoptosis by reducing oxidative stress and inflammation, and also help prevent CIR injury. On the basis of our hypothesis, we combined the results of transcriptomic and metabonomic analyses and found that ASE and GEB could prevent cerebral ischemia-reperfusion injury induced by middle cerebral artery occlusion by targeting phenylalanine, pyrimidine, methionine, and sphingolipid metabolism. This study provides the basis for the compatibility and efficacy of ASE and GEB.